Analysis of the Role of Waiters and Waitresses in Improving Service Quality at Kasasa Restaurant at Paradise Hotel Golf & Resort - Sawelo, Cecilia Gloria; Sangari, Fonny Erny Helty; Pua, Marten Maxi; Lumataw, Jane Arthur (International Journal of Strategic Studies, 2024)
A restaurant is a place or building organized commercially, providing exemplary service to all its guests, both food and drink. This study aims to analyze the role of Waiters and Waitresses in improving the quality of service at Kasasa Restaurant at Paradise Hotel Golf and Resort. This study uses a descriptive qualitative method and assessment analysis. The results of this study indicate that Waiters and Waitresses have a role in greeting guests, serving food, tidying up, and serving guests well. In order to improve the quality of service at Kasasa Restaurant, all stages of service activities are expected to be implemented to serve guests as optimally as possible. For this reason, more training is needed from the supervisor or manager to the staff and interns at the food and beverage service department at Derpartermernt.